2011
DOI: 10.1586/eri.11.92
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a causal relationship between respiratory syncytial virus infection and asthma

Abstract: Respiratory syncytial virus (RSV) infects all children early in life, is the most common cause of infant lower respiratory tract infections, and causes disease exacerbations in children with asthma. Episodes of lower respiratory tract infection in early life are associated with asthma development. Whether RSV infection early in life directly causes asthma or simply identifies infants who are genetically predisposed to develop subsequent wheezing is debatable. Recent studies suggest that these two explanations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
152
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 126 publications
2
152
0
5
Order By: Relevance
“…The mechanisms underlying the interaction between RSV-LRI in early childhood and active smoking as determinants of asthma in early adult life are unknown, and they cannot be definitively established in an epidemiologic study like ours (37). A first possibility is that early life RSV illness may play a direct role by altering immune responses and/or inducing airway injury, which would predispose the host to asthma, impaired lung function, and airway hyperreactivity on exposure to cigarette smoking in adulthood.…”
Section: Discussionmentioning
confidence: 88%
“…The mechanisms underlying the interaction between RSV-LRI in early childhood and active smoking as determinants of asthma in early adult life are unknown, and they cannot be definitively established in an epidemiologic study like ours (37). A first possibility is that early life RSV illness may play a direct role by altering immune responses and/or inducing airway injury, which would predispose the host to asthma, impaired lung function, and airway hyperreactivity on exposure to cigarette smoking in adulthood.…”
Section: Discussionmentioning
confidence: 88%
“…We and others have previously compiled the genes that have been demonstrated to be associated with RSV and asthma. Among these are polymorphisms in a number of immune response genes, suggesting immune perturbations common to both diseases : CX3CR1, TLR-4, SP-A, SP-D, IL-10, CCR5, TLR-10, IL-4, IL-13, IL-10, IL-8, IL-18, tumor necrosis factor, TLR-4, MS4A2, VDR, IL-4Ra, RANTES, TGF-b1, and ADAM33 (14,15). In addition, a recent clinical multicenter cohort study found that human IL1RL1 gene variants and nasopharyngeal IL1RL1-a levels were associated with severe RSV bronchiolitis.…”
Section: Host Genetic and Familial Determinants Linking Infant Rsv Anmentioning
confidence: 99%
“…The GA3 clade has been associated with greater severity of illness compared with clades GA2 and GA4 (41). Differential pathogenesis of RSV A subgroup strains has been reported in an animal model of infection of BALB/cJ mice with RSV A2001/2-20 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A subgroup strain resulted in greater disease severity, higher lung IL-13 levels, and higher lung gob-5 levels and induced airway mucin expression, supporting differential pathogenicity dependent on strain in these genetically identical mice (42).…”
Section: Viral Strain Determinants Of Infant Infection Severity and Amentioning
confidence: 99%
“…In addition to genetic factors, however, it is clear that early-life exposure to pathogens such as respiratory syncytial virus can contribute to the development of asthma (10,11). A variety of other airborne exposures can exacerbate asthma, such as house dust mite (HDM), cigarette smoke, and fungal species (12).…”
mentioning
confidence: 99%